Industrial biotransformations catalyzed by microbial lipases: screening platform and commercial aspects - Abdulhamid, María Belén; Costas, Luciana; Del Valle Loto, Flavia; Baigorí, Mario Domingo; Pera, Licia María (Folia microbiologica, 2021)
The successfulness of a lipase-catalyzed industrial process depends on a proper lipase selection. In this work, an alternative screening platform for industrially important biotransformations catalyzed by microbial lipases was proposed. Thus, the reactivity of sixty lipase activities from spore-forming microorganisms towards hydrolytic and transesterification reactions by using p-nitrophenyl palmitate as a chromogenic acyl donor substrate was explored. Only three biocatalysts were capable of catalyzing all reactions tested. Fourteen biocatalysts did not show hydrolytic activity at all; however, they displayed transesterification activities using ethanol, starch, low-methoxyl (LM) pectin, high-methoxyl (HM) pectin, or vitamin C as acyl acceptors. Using heat-treated biocatalysts, hydrolytic activities were not highly correlated with the corresponding transesterification activities using ethanol (r = -0.058, p = 0.660), starch (r = 0.431, p = 0.001), LM pectin (r = -0.010, p = 0.938), HM pectin (r = 0.167, p = 0.202), and vitamin C (r = -0.048, p = 0.716) as acyl acceptor. In addition, to the best of our knowledge, several transesterification activities produced from microorganisms of the genus Bacillus, Brevibacillus, Lysinibacillus, Geobacillus, or Sporosarcina were reported for first time. Finally, the global lipase market was presented and segmented by date, application, geography and player highlighting the commercial contribution of microbial lipases.
Keywords: Biotransformation; Catalysis; lipasa; Esterification; Lipase; hydrolýza; esterifikace; Hydrolysis; katalýza; biotransformace